Eksistensi KPK dalam Peradiian Korupsi di Indonesia - Muhammad Abdul Kholiq (Fakultas Hukum Universitas Islam Indonesia, 2004)
The existence of KPK based on the act No. 30/2002 is aimed to be special super body organization to optimize in wiping out corruption inIndonesia. The special features are-: caused first the institution of law up holder existed(c.c policeand attorney) is dependent institutionally because of the position is underthe executive (c.qPresident); second, the action, of law enforcement forthe corruption criminal by both institution tend to show theirrecklessness. In other words;it is not effective, efficient and optimal and it has bom pessimistic for the public as well about law supremacy especially in wiping out the corruption practices. Toenhance the public trust as well as the prestige of KPK it self, so KPK must wipe out the corruption practices continuously without any compromising but is must be suitable with the task and authority given by legislation.